2004
DOI: 10.1161/01.cir.0000109484.00668.ce
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Effects of a QT-Prolonging Drug, Arsenic Trioxide, on Cardiac Potassium Currents

Abstract: Background-Cases of QT prolongation, torsades de pointes, and sudden death have been reported with arsenic trioxide (As 2 O 3 ), a highly effective agent for acute promyelocytic leukemia. In this study, we evaluated the effects of As 2 O 3 on repolarizing cardiac ion currents. Methods and Results-In HERG-or KCNQ1ϩKCNE1-transfected CHO cells (nϭ32; total), As 2 O 3 caused concentrationdependent block of both I Kr and I Ks , with an IC 50 for tail current block of 0.14Ϯ0.01 mol/L for I Kr and 1.13Ϯ0.06 mol/L for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
65
2
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 16 publications
6
65
2
2
Order By: Relevance
“…This work amplifies the recent report by Rampe and co-workers (Kuryshev et al, 2005), who also showed that low concentrations of pentamidine selectively disrupted protein trafficking and maturation of KCNH2 channels but not of hKv1.5, KvLQT1/minK and Kv4.3 channels, and that in isolated guinea pig ventricular myocytes culture in pentamidine (10 mM) prolonged action potential duration and reduced I Kr . Taken together, these two papers provide clear evidence of a novel mechanism for causing druginduced LQTS; disruption of KCNH2 channel protein trafficking to reduce surface membrane expression of functional channels.For at least one other drug, arsenic trioxide, disruption of normal KCNH2 channel protein processing has been implicated as a mechanism for drug-induced LQTS (Ficker et al, 2004), although arsenic trioxide has also been reported to directly block KCNH2 channels (Drolet et al, 2004). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This work amplifies the recent report by Rampe and co-workers (Kuryshev et al, 2005), who also showed that low concentrations of pentamidine selectively disrupted protein trafficking and maturation of KCNH2 channels but not of hKv1.5, KvLQT1/minK and Kv4.3 channels, and that in isolated guinea pig ventricular myocytes culture in pentamidine (10 mM) prolonged action potential duration and reduced I Kr . Taken together, these two papers provide clear evidence of a novel mechanism for causing druginduced LQTS; disruption of KCNH2 channel protein trafficking to reduce surface membrane expression of functional channels.For at least one other drug, arsenic trioxide, disruption of normal KCNH2 channel protein processing has been implicated as a mechanism for drug-induced LQTS (Ficker et al, 2004), although arsenic trioxide has also been reported to directly block KCNH2 channels (Drolet et al, 2004). …”
mentioning
confidence: 99%
“…For at least one other drug, arsenic trioxide, disruption of normal KCNH2 channel protein processing has been implicated as a mechanism for drug-induced LQTS (Ficker et al, 2004), although arsenic trioxide has also been reported to directly block KCNH2 channels (Drolet et al, 2004).…”
mentioning
confidence: 99%
“…In another study, the prevalence of QTc prolongation in arsenic-exposed people was reported as 90% (24) and the underlying mechanisms of arsenic cardiotoxicity have been suggested as excessive generation of oxygen free radicals and oxidative stress (6,24).…”
Section: Discussionmentioning
confidence: 99%
“…1,3 The prolongation of the QTc interval appears to be due to a concentration-dependent blockade of IKr and IKs potassium currents compromising repolarisation and increasing electrical susceptibility to ventricular arrhythmias. 4 Arsenic has also been shown to activate a time-independent IK-ATP which maintains normal repolarisation. The variability in QTc prolongation as well as the onset of ventricular arrhythmias likely represent competing activation and blockade of potassium channels during ventricular repolarisation.…”
Section: Discussionmentioning
confidence: 99%
“…The variability in QTc prolongation as well as the onset of ventricular arrhythmias likely represent competing activation and blockade of potassium channels during ventricular repolarisation. 4 The susceptibility for ventricular pro-arrhythmia has been postulated to be linked to electrolyte abnormalities, specifically hypokalaemia and hypomagnesaemia, as well as concomitant treatment with QTc-prolonging medications.…”
Section: Discussionmentioning
confidence: 99%